Presacral myelolipoma as a possible parasymptom of cancer: A case report. (20th April 2018) - Sakamoto, Akio; Nagamatsu, Iori; Shiba, Eisuke; Okamoto, Takeshi; Hisaoka, Masanori; Matsuda, Shuichi
Presacral myelolipomas are rare, benign, asymptomatic tumors composed of mature adipose tissue and hematopoietic elements. Presacral myelolipomas can occur in patients with a medical history of malignancy, steroid use, and/or endocrine disorders including diabetes mellitus. A 65-year-old man with no specific medical history experienced temporal abdominal pain without bowel symptoms that lasted a few hours. By the time he visited a hospital, the pain had diminished. Computed tomography failed to detect any abnormality in the abdominal or pelvic organs that would have caused the abdominal pain but revealed a lesion 4 cm in diameter in the frontal sacrum. Magnetic resonance imaging showed that the lesion contained fat elements with a high signal intensity on T1- and T2-weighted images, which was decreased on fat-suppression T2-weighted images. Computed tomography–guided biopsy and imaging allowed a diagnosis of presacral myelolipoma. After 3 months, hematochezia was observed, and follow-up examination revealed rectal carcinoma with multiple lung metastases. He died due to spread of the cancer despite chemotherapy, 6 months after the cancer was found. Considering the possible association between presacral myelolipoma and cancer, presacral myelolipoma might be a cancer parasymptom. Checking for possible malignancy may therefore be warranted in patients with presacral myelolipoma, especially in those without diabetes mellitus.